Archaeology of the "Social Commitment" Concept within the Pedagogical and Teachers' Training Discourse - Jaume Martínez Bonafé (Universidad Autónoma de Baja California, 2001)
The text invites the reader to undertake a genealogical research on the ways the pedagogical discourse has neglected some teaching driving principles, such as the educators' political commitment. It shows the role played by certain reformatory policies in the process of institutional perversion. The analysis of what is said and what is kept from saying, of which forms of pedagogy are silenced and which ones are promoted along the reformation process, is a good way to understand the close relationship between knowledge and power within the structure of the dominant discourse about schools and teachers.